Modalities of corruption of the private sector. An expanding phenomenon in the Latin American environment (Revista Científica Compendium, 2022)
The phenomenon of corruption in the Latin American context has been expanding. One of the origins of the problem is the eagerness of private companies to expand the market and increase financial returns. Based on the search for information consulted in scientific databases, the objectives of this article were: a) analyze the modalities of corruption in the private sector, b) establish quantitative and qualitative comparisons between corruption in the public and private sectors, and c) identify the typologies of crimes and investigate the characterization of the profile of white-collar criminals who commit illicit acts in this sector. To mitigate the phenomenon of private corruption, an analysis of the multidisciplinary causes that induce corrupt individuals to divert their behavior to produce goods and services without social responsibility, putting private interests first, is required.
Keywords: Corruption; Delinquency; Private enterprises; Private sector; Social Responsibility